The health effects of a youth labor market activation policy - Caroline King Barnard Hall; Kaisa Kotakorpi; Linus Liljeberg; Jukka Pirttilä (Institute for Evaluation of Labour Market and Education Policy (IFAU), 2024)
We examine the health effects of a labor market activation policy, the Youth Job Guarantee, implemented in Sweden in 2007. To estimate the causal effects of this policy on health, we implement an RD-design using the age-eligibility threshold of the policy, together with detailed administrative data on health outcomes including measures of mental health. Health effects could arise indirectly via effects on employment, or directly, e.g., via an improved daily routine. In contrast to most of the existing literature on the health effects of ALMPs, our results indicate that the activation policy did not have clear positive effects on health one year after the start of the unemployment spell, measured by prescribed medication or healthcare visits.
Keywords: J68; I12; I18; H51; 330; Labor market programs; activation; youth unemployment; mental health